Causal Effect of the Triglyceride-Glucose Index and the Joint Exposure of Higher Glucose and Triglyceride With Extensive Cardio-Cerebrovascular Metabolic Outcomes in the UK Biobank: A Mendelian Randomization Study - Si, Shucheng; Li, Jiqing; Li, Yunxia; Li, Wenchao; Chen, Xiaolu; Yuan, Tonghui; Liu, Congcong; Li, Hongkai; Hou, Lei; Wang, Bojie; Xue, Fuzhong (Frontiers in Cardiovascular Medicine, 2021)
Background The causal evidence of triglyceride-glucose (TyG) index, as well as the joint exposure of higher glucose and triglyceride on the risk of cardio-cerebrovascular diseases (CVD), was lacking. Methods A comprehensive factorial Mendelian Randomization (MR) was performed in the UK Biobank cohort involving 273 368 individuals with European ancestry to assess and quantify these effects. The factorial MR, MR-PRESSO, MR-Egger, meta-regression, sensitivity analysis, positive control, and external verification was utilized. The outcomes including the major outcome: overall CVD, ischaemic heart diseases (IHD), and cerebrovascular diseases (CED), and minor outcome: angina pectoris (AP), acute myocardial infarction (AMI), chronic IHD (CIHD), heart failure (HF), hemorrhagic stroke (HS), and ischaemic stroke (IS). Results The TyG index significantly increased the risk of overall CVD [OR(95%CI): 1.20(1.14-1.25)], IHD [OR(95%CI): 1.22(1.15-1.29)], CED [OR(95%CI): 1.14(1.05-1.23)], AP [OR(95%CI): 1.29(1.20-1.39)], AMI [OR(95%CI): 1.27(1.16-1.39)], CIHD [OR(95%CI): 1.21(1.13-1.29)], and IS [OR(95%CI): 1.22(1.06-1.40)]. Joint exposure to genetically higher GLU and TG was significantly associated with a higher risk of overall CVD [OR(95%CI): 1.17(1.12-1.23)] and IHD [OR(95%CI): 1.22(1.16-1.29)], but not with the CED. The effect of GLU and TG was independent of each other genetically and presented dose-response effects in bivariate meta-regression analysis. Conclusions Lifelong genetic exposure to higher GLU and TG was jointly associated with higher cardiac metabolic risk while the TyG index additional associated with several cerebrovascular diseases. The TyG index could be served as a more sensitive pre-diagnostic indicator for CVD while the joint GLU and TG could offer a quantitative risk for cardiac metabolic outcomes.